The Effect of Microbial Endophyte Consortia on Pseudotsuga menziesii and Thuja plicata Survival, Growth, and Physiology Across Edaphic Gradients - Aghai, Matthew M.; Khan, Zareen; Joseph, Matthew R.; Stoda, Aubrey M.; Sher, Andrew W.; Ettl, Gregory J.; Doty, Sharon L. (Frontiers in Microbiology, 2019)
Increased frequency of droughts and degraded edaphic conditions decreases the success of many reforestation efforts in the Pacific Northwest. Microbial endophyte consortia have been demonstrated to contribute to plant growth promotion and protection from abiotic and biotic stresses – specifically drought conditions – across a number of food crops but for limited tree species. Our research aimed to investigate the potential to improve establishment of economically and ecologically important conifers through a series of in situ field trials and ex situ simulations. Microbial endophyte consortia from Salicaceae, previously shown to confer drought tolerance, and conifer endophyte strains with potentially symbiotic traits were selected for trials with Douglas-fir (Pseudotsuga menziesii) and western redcedar (Thuja plicata). Reductive experimentation was used to subject seedlings to a spectrum of simulated drought levels or presence/absence of fertilizer, testing hypotheses that endophyte consortia impart improved drought resistance and growth promotion, respectively. Inoculation from Salicaceae consortia significantly (p0.05) improved survival among seedlings of both species subject to increasing drought stress, with T. plicata seedlings surviving at two-fold higher rates in extreme drought conditions. Both species demonstrated improved growth 540 days after inoculation of seed with conifer derived consortia. In the carefully controlled greenhouse experiments with both species, seedling Fv/Fm and SPAD values remained significantly (p0.05) more stable in inoculated treatment groups as stress increased. Our findings confirm that multi-strain consortia may be applied as seed or field amendment to conifers, and the approach is efficient in garnering a positive growth response and can mitigate abiotic stressors.